Aptamers Selected by Cell-SELEX for Theranostics - Tan, Weihong (Springer, 2015)
This edited volume describes cell-SELEX as the fundamental tool used to generate aptamer molecules for a wide range of applications in molecular medicine, bioanalysis and chemical biology. Easily integrated into the natural heterogeneous cell matrix, aptamers can be effectively used in theranostics, bioanalysis, environment detection and biomedical studies. The book gathers reviews that reflect the latest advances in the field of aptamers and consists in fourteen chapters demonstrating essential examples of these aptamers and aptamer-nanomaterial assemblies, depending on the types of applications and biological systems. It also includes a separate chapter on the utilization of aptamers in real clinics and what will be required to achieve this significant goal. The book will be both appealing and useful to a broad audience, including biologists, bioscientists, and clinicians whose interests range from chemistry and biomedical engineering to cell and molecular biology and biotechnology.